Arithmetic fact retrieval and working memory in schizophrenia - Kiefer, Markus; Apel, Andrea; Weisbrod, Matthias (Schizophrenia research, 2002)
Despite its importance in every-day life and vocational rehabilitation, arithmetic ability has rarely been investigated in schizophrenic patients. Those few studies reporting arithmetic deficits in schizophrenia, however, administered complex calculation tasks which drew not only on arithmetic abilities, but also on working memory resources known to be impaired in schizophrenia. In the present study, arithmetic abilities and working memory functions were investigated in schizophrenic patients (n=24) and healthy control subjects (n=24). Arithmetic fact retrieval was assessed in single-digit multiplication and corresponding division problems using a result verification task which minimized working memory demands. Problem size and the disparity of the proposed result were manipulated. The storage component of working memory was tested with a digit span forward task and the executive control component with a digit span backward as well as with verbal fluency tasks. Schizophrenic patients performed worse than controls only in the executive tasks. Digit span forward was preserved. In the arithmetic tasks, groups did not differ from each other, and a similar pattern of task manipulations was obtained. Hence, despite the executive control deficit retrieval of arithmetic facts is preserved in schizophrenia. Moreover, the same underlying cognitive processes as in control subjects are involved.